DETERMINAN EFEKTIVITAS IMPLEMENTASI ANGGARAN BERBASIS KINERJA DAN PENYERAPAN ANGGARAN DI PEMERINTAH DAERAH - Novrian Dandi Pratama; Ahim Abdurahim; Hafiez Sofyani (Jurnal Reviu Akuntansi dan Keuangan, 2018)
This study aims to attempt influence of  Understanding, Training, and External Pressure to the Effectiveness of Performance-Based Budgeting Implementation and Budget Realization in Province Government of Yogyakarta Special Rebion. Respondents representing the sample are head, secretary, expense treasurer, and head of planning subdepartment of agency at Local Government Unit (SKPD). Data was obtained by questioner dispersion technique to respondent. The collected quistioner was 113. Hypothesis testing employs Structural Equation Model (SEM) approach. The results show that education, understanding, training, and external pressure are the factors that have significant effect on the effectiveness of performance-based budgeting implementation. For budget realization, the understanding and effectiveness of performance-based budgeting implementation are two aspects that have significant effect.